Conceptualizing ecosystem degradation using mangrove forests as a model system. (November 2021) - Yando, Erik S.; Sloey, Taylor M.; Dahdouh-Guebas, Farid; Rogers, Kerrylee; Abuchahla, Guilherme M.O.; Cannicci, Stefano; Canty, Steven W.J.; Jennerjahn, Tim C.; Ogurcak, Danielle E.; Adams, Janine B.; Connolly, Rod M.; Diele, Karen; et al.
Abstract: The status and potential degradation of an ecosystem is often difficult to identify, quantify, and characterize. Multiple, concurrent drivers of degradation may interact and have cumulative and confounding effects, making mitigation and rehabilitation actions challenging to achieve. Ecosystem status assessments generally emphasize areal change (gains/losses) as a primary indicator; however, this over-simplifies complex ecosystem dynamics and ignores metrics that would better assess ecosystem quality. Consideration of multiple indicators is necessary to characterize and/or anticipate ecosystem degradation and appropriately identify factors causing changes. We utilize mangrove forests as a model system due to their distribution across a wide range of geographic settings, their position in the inherently dynamic coastal zone, and the multiple natural and anthropogenic pressures they face. We present a conceptual framework to: i) examine drivers of ecosystem degradation and characterize system status, and ii) delineate the roles of biogeographic and geomorphic variability, site history and typology, and references. A complementary workflow is proposed for implementing the conceptual framework. We demonstrate the universal applicability of our conceptual framework through a series of case studies that represent locations with differing drivers of degradation and biogeographic and geomorphic conditions. Our conceptual framework facilitates scientists, conservation practitioners, and other stakeholders in considering multiple aspects of ecosystems to better assess system status and holistically evaluate degradation. This is achieved by critically evaluating suitable comparisons and relevant elements in assessing a site to understand potential actions or the outcome of previously implemented management strategies. Graphical abstract: Unlabelled Image Highlights: Assessing degradation can be improved by understanding both drivers of degradation and overall system status We provide a framework that compares indicators of degradation and system status using mangrove forests as a model system The framework was applied to six global locations showcasing it's flexibility to utilize existing data from varied sources The conceptual framework can inform scientists, practitioners, and other stakeholders as they monitor and manage their system